Intention to drink and alcohol use before 18 years among Australian adolescents: An extended Theory of Planned Behavior. (December 2020) - Zhao, Xiang; Kelly, Adrian B.; Rowland, Bosco; Williams, Joanne; Kremer, Peter; Mohebbi, Mohammadreza; Carter, Rob; Abraham, Charles; Abimanyi-Ochom, Julie; Toumbourou, John W.
Highlights: The extended model accounted for 60% variance in adolescent alcohol use. Stricter parental rules predicted lower adolescent intention to consume alcohol. Stricter parental rules predicted stronger adolescent anti-alcohol attitudes. Community attitudes had a stronger influence on boys' anti-alcohol attitudes. Parental rules were less influential in reducing alcohol use in older adolescents. Abstract: Introduction: Preventing adolescent alcohol use is an international public health priority. To further understand adolescent alcohol use, this study tested a model of adolescent intention to consume alcohol that incorporated multiple social systems influences. Methods: Participants included 2529 Australian secondary school students ( M age  = 14.20; 53.7% female). Participants completed a survey about risk and protective factors for alcohol use at individual, family, school and community levels. Structural Equation Modeling (path analysis) was used to evaluate an extended Theory of Planned Behavior (TPB) that incorporated social system determinants of intention to consume alcohol. Results: The final model explained 60% of the variance in adolescent alcohol use intention. All TPB constructs correlated with intention and experience of lifetime alcohol use. More exposure to information about alcohol use had a weak but significant influence on adolescents' stronger perceived behavioral control. Having less friends who use alcohol, stricter parental rules for adolescent alcohol use, and unfavorable parent attitudes towards alcohol use, were associated with stronger adolescent anti-alcohol attitudes and subjective norms. Community level pro-abstinence attitudes predicted unfavorable adolescent attitudes to alcohol and intention to consume alcohol. Parental rules showed significantly stronger influences on alcohol use intention amongst younger adolescents. Conclusions: Key social systems around adolescents significantly predicted intention to consume alcohol, and the extended TPB model explained the major variance in adolescent alcohol use. The findings emphasize the importance of multi-level approaches to the prevention of alcohol use. Situation-based factors that could trigger impulsive emotional response may be a future intervention focus.